Mediastinal tuberculosis in adult: case report - Singh, Gurminder; Joshi, Neeraj; Garg, Robin; Garg, Sudhanshu (International Journal of Research in Medical Sciences, 2017)
Mediastinal lymph node enlargement commonly seen in sarcoidosis, lung cancer, lymphoma and tuberculosis in children’s. Tuberculosis in adult mostly involve parenchyma of lung and very rarely involve mediastinal lymph nodes, here we report a 27-year-old male, non-diabetic, non-hypertensive, non-alcoholic and non-smoker who present with low grade fever and dry cough. Search for the cause of morbidity revealed him to be suffering from mediastinal tuberculosis. He was treated for tuberculosis with ATT.